Integration of conventional cytogenetics, comparative genomic hybridisation and interphase fluorescence in situ hybridisation for the detection of genomic rearrangements in acute leukaemia. Issue 8 (12th May 2008) - McGrattan, P; Campbell, S; Cuthbert, R; Jones, F G C; McMullin, M F; Humphreys, M
Abstract : Aims: To screen for genomic imbalances in patients with acute leukaemia using conventional (G-banding) and molecular (comparative genomic hybridisation (CGH) and fluorescence in situ hybridisation (FISH)) methods to determine whether an integrative screening approach increases abnormality detection rate. Methods: G-banded analysis was performed on unstimulated bone marrow (BM) or peripheral blood (PB) cells after short-term (24-hour) culture. CGH was performed on reference (control) and neoplastic (test patient) genomic DNA extracted from BM or PB samples. Interphase FISH (i-FISH) was selectively carried out at disease diagnosis on patients with acute lymphoblastic leukaemia and acute myeloid leukaemia using conventional methods. Results: Genomic rearrangements were detected in 4, 7 and 6 patients using G-banding, CGH and i-FISH respectively. Discordance in results between G-banding, CGH and/or i-FISH was found in 7 of the 12 patients screened. G-banding and CGH, when used individually, detected a genomic imbalance/rearrangement in 33.3% and 58.3%, respectively, of the patients screened. However, when both screening methods were integrated, the abnormality detection rate increased to 66.7%. This detection rate increased further to 75.0% with the use of i-FISH screening. Conclusions: The advantages and disadvantages of using G-banding, CGH and i-FISH as either stand-alone or integrated screening methods for the detection and characterisation of genomic imbalances in acute leukaemia are clearly demonstrated. Abnormality detection rate significantly increased when an integrated screening approach was employed which could potentially provide valuable information for risk stratification in patients with acute leukaemia.